2018
DOI: 10.1039/c7py02064c
|View full text |Cite
|
Sign up to set email alerts
|

Labeling of native proteins with fluorescent RAFT polymer probes: application to the detection of a cell surface protein using flow cytometry

Abstract: Fluorescent RAFT polymer probes with an activated ester reactive end-group can be advantageously used to label native proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
0
20
1
Order By: Relevance
“…As we previously reported that such polymer probes bearing AF647 fluorophores (but without the Halo-ligand) were not cell permeant, 5 this study was conducted with HeLa S3 cells engineered 21 to express the HaloTag at the cell surface with a GPI-anchor (Halo-GPI cells) (see Methods). Expression of the HaloTag transgene in the Halo-GPI cells was either induced with 50 nM doxycycline (Dox) for 48 h or not induced (negative control) followed by incubation with two types of fluorescent probes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we previously reported that such polymer probes bearing AF647 fluorophores (but without the Halo-ligand) were not cell permeant, 5 this study was conducted with HeLa S3 cells engineered 21 to express the HaloTag at the cell surface with a GPI-anchor (Halo-GPI cells) (see Methods). Expression of the HaloTag transgene in the Halo-GPI cells was either induced with 50 nM doxycycline (Dox) for 48 h or not induced (negative control) followed by incubation with two types of fluorescent probes.…”
Section: Resultsmentioning
confidence: 99%
“…4c The polymer chain size can be controlled owing to the RAFT polymerization process. In addition, we have already shown that such polymer chains can be functionalized at their chain end to promote an oriented conjugation onto native proteins 5 or histidine-tagged proteins in vitro via a nitrilotriacetic acid (NTA) ligand. 6…”
Section: Introductionmentioning
confidence: 99%
“…These polymers were synthesized from the same PNAM precursor bearing a succinimidyl ester chain-end (noted 0 in Scheme 2) prepared following a previously described procedure. 10 MALDI-TOF MS was then used to prove the chain-end modification, especially by conducting negative-ion analyses with non-stabilized THF.…”
Section: Resultsmentioning
confidence: 99%
“…A significant effort in the field was done to develop bright staining reagents by employing multimerization of smallmolecule fluorophores on non-fluorescent polymeric backbones such as polymethacrylate derivatives, [113] copolymers of Nacryloylmorpholine and N-acryloxysuccinimide (poly(NAM-co-NAS)), [114] and many others [115][116][117] (Figure 6, Table 6). The requirements to these dyes are often similar to those of π-conjugated polymers, e. g. high water-solubility, presence of bioconjugation [a] M n .…”
Section: Polymer-based Fluorophore Multimersmentioning
confidence: 99%